Developing decentralized capacity for disaster prevention: lessons from food security and nutrition monitoring in Malawi - Babu, Suresh Chandra; Mthindi, Gadson B. (Wiley, 1995)
Lack of sufficient analytical capacity in most of the countries of sub‐Saharan Africa has been frequently mentioned as a major factor limiting the effectiveness of drought management interventions. In this article we describe an approach used in Malawi for the past three years to develop a decentralized capacity to analyse drought management and disaster prevention programmes. A conceptual framework is presented which identifies the areas in which capacity strengthening is required and lessons from the Malawi experience are presented. Various issues relating to the efficiency of capacity building programmes are discussed. We argue that continuous dialogue between development researchers and decision‐makers, and between trainers in academic institutions and donor agencies, is essential for achieving the goals of improved capacity for drought management and disaster prevention.